Economics of information and knowledge - Lamberton, D.M. (Middlesex: Penguin, 1971)
The economics of information and knowledge is rapidly emerging as a vital topic in modern society, analyzing as it does the processes by which information is produced stored, used an misused. This collection of Readings discusses these points in depth. Part One contains two surveys of ideas on the subject while the Readings in Part Two explore the way in which information interacts with economic organization. An assessment of the efficiency of resource allocation to knowledge acquisition and utilization is provided in Part three. Part Four contains an examination of the two fold function of documentation and transfer in information policy. Readings on the international aspects appear in Part Five. Part Six is devoted to usefulness planning, procedures of long range on casting, optimization techniques and innovation. The Concluding Part is a cogent piece by Shubik calling for rethinking of some of out models of political and economic man so that they suit the pattern of the uncertain decision maker acting under severely restricted conditions of information.
Part One Two surveys -- Part Two Economic Organization -- Part Three Information and Efficiency -- Part Four Information Policy -- Part Five International Aspects -- Part Six Business Planning -- Part Seven Conclusion
Includes index
Keywords: Economics; Information and knowledge